2022
DOI: 10.48550/arxiv.2205.00724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic qubit allocation and routing for constrained topologies by CNOT circuit re-synthesis

Abstract: Many quantum computers have constraints regarding which two-qubit operations are locally allowed. To run a quantum circuit under those constraints, qubits need to be allocated to different quantum registers, and multi-qubit gates need to be routed accordingly. Recent developments have shown that Steiner-tree based compiling strategies provide a competitive tool to route CNOT gates. However, these algorithms require the qubit allocation to be decided before routing. Moreover, the allocation is fixed throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Finally, through a series of computational experiments, we demonstrated that for large circuits our quantum comb generalisation of RowCol outperforms the slicing procedure on a range of architectures and CNOT/non-CNOT proportions. Work has recently been done on improving the performance of RowCol by allowing the qubits to be permuted by the synthesis algorithm [10], investigating whether the performance of CombSynth could be improved in a similar way would be an interesting research direction. Currently, comb synthesis is designed to work with a subroutine that only works with one qubit (and hence one row/column) at a time, but it would be worth adapting it to work with synthesis algorithms which operate one more than one row or column at once, like the Patel-Markov-Hayes algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, through a series of computational experiments, we demonstrated that for large circuits our quantum comb generalisation of RowCol outperforms the slicing procedure on a range of architectures and CNOT/non-CNOT proportions. Work has recently been done on improving the performance of RowCol by allowing the qubits to be permuted by the synthesis algorithm [10], investigating whether the performance of CombSynth could be improved in a similar way would be an interesting research direction. Currently, comb synthesis is designed to work with a subroutine that only works with one qubit (and hence one row/column) at a time, but it would be worth adapting it to work with synthesis algorithms which operate one more than one row or column at once, like the Patel-Markov-Hayes algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis algorithms provide a means of reducing the size of CNOT circuits [15], or allow the resynthesis of circuits under topological constraints [11,14,10]. The ability to perform both of these tasks efficiently is vital for NISQ computing, as it provides a way to best utilise the machines we have available whilst minimising the consequences of their limitations.…”
Section: Cnot Circuit Synthesis Algorithmsmentioning
confidence: 99%
See 2 more Smart Citations